Experimental and Numerical Analysis of Carbon/Epoxy Composite Plate Subject to Low-Velocity Impact - Muhamad Giri Suada; Hendri Syamsudin; Haroen Romadon (Journal of Engineering and Technological Sciences, 2022)
The present work compared experimental and finite element analysis on the low-velocity impact response of a carbon/epoxy composite plate. Finite element analysis was based on the utilization of cohesive zone elements with the Benzeggagh-Kenane fracture criterion to predict the initiation and propagation of delamination. A Kirchhoff based formulation of a continuum shell element was used to model the stiffness of each lamina and the Hashim-Rotem damage mechanism to predict damages in every lamina. Five specimens of a 16-layer uni-directional carbon/epoxy composite plate with fiber orientation [+45°/90°/-45°/0°/+45°/90°/-45°/0°] s were subjected to low-velocity impact with a single energy value of 2.75 Joule/mm. The experimental results were then compared to the finite element results. Good agreement was achieved for the size and shape of the total projected delamination and visual damage to the top and bottom surface in the form of matrix and fiber failure. Slight differences were found for the dynamic response in the impact force history. Furthermore, a significant difference was found for the quantity of absorbed energy.